Experimental Study of Retention on the Combination of Bifidobacterium with High-Intensity Focused Ultrasound (HIFU) Synergistic Substance in Tumor Tissues - Gao, Xuan (Sci Rep, 2019)
High intensity focused ultrasound (HIFU) has been recently regarded to be a new type of technique for non-invasive ablation of local tumors and HIFU synergists could significantly improve its therapeutic efficiency. The therapeutic efficiency of HIFU is greatly limited by the low retention of HIFU synergists in the target area and short residence time. This study aimed to explore a method to increase the deposition of HIFU synergists in tumors. Cationic lipid nanoparticle can be used to enhance the HIFU ablation effect, but there is still a problem for it that the deposition amount in the tumor tissue is small and the residence time is short. Bifidobacterium is highly biosafe and can be selectively colonized in the hypoxic zone of tumor tissue. Cationic lipid nanoparticles can be observed in vitro by attachment to bifidobacterium by electrostatic adsorption. And the effect of the proliferation of bifidobacterium in tumor tissues on the retention amount and retention time of cationic lipid nanoparticles in vivo was evaluated. Results showed that the cationic lipid nanoparticles were linked to the surface of Bifidobacterium effectively in vitro, while in vivo, the retention amount and retention time of cationic lipid nanoparticles could be increased by Bifidobacterium in tumor tissues, which provided a new method for improving the therapeutic efficiency of HIFU.